PENGARUH KOMPETENSI KOMUNIKASI, KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PERSONEL POLSEK KEDUNDUNG KABUPATEN SAMPANG - jurnalmap map; Ali Sibro Mulisi (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2020)
This research was conducted at Kedungdung Sub-District Police, Sampang Regency. with a total sample of 33 people. The objectives of this study are: 1) to find out and describe communication competencies, emotional intelligence, organizational culture and performance of Kedungdung police officers in Sampang District, 2) to find out and analyze whether communication competencies, emotional intelligence and organizational culture simultaneously influence the performance of Kedungdung police officers in Sampang District, 3) to find out and analyze whether communication skills, emotional intelligence and organizational culture partially influence the performance of the Kedungdung police officers in Sampang Regency. The results showed that 1). Simultaneously, communication competencies, emotional intelligence and organizational culture had a very significant effect on employee performance. 2). Partially, communication competencies, emotional intelligence and organizational culture have a significant influence on the performance of Kedungdung Police officers in Sampang Regency. Thus, it can be said that all independent variables partially have a significant influence on the performance of the Sampang District Police officers; 3) organizational culture variable has a dominant influence to the performance of the apparatus in the Kedungdung Police Sector in Sampang Regency. Keywords: competence of communication, emotional intelligence, organizational culture, performance of Personnel.